Negative Marketing in The Softdrink Industry: The Effect of Greenwashing Perceptions on Purchase Intention Through Brand Image on Sprite - Chandra, Eric; Novita, Novita (Dinasti Publisher, 2024)
This study examines the impact of greenwashing perceptions on consumer purchase intention for eco-friendly soft drinks in Jakarta, with brand image as a moderating variable. Although the public is increasingly aware of the importance of eco-friendly products, corporate marketing practices have not supported this trend. Using descriptive and quantitative methods, with 73 respondents selected through purposive sampling and analyzed using SmartPLS 3.2.9, the results show that greenwashing perceptions affects brand image but does not influence purchase intention. Brand image also does not affect purchase intention or mediate the relationship between greenwashing and purchase intention. In conclusion, transparency and sustainability are crucial to avoiding greenwashing and enhancing brand image and consumer purchase intention.